Percutaneous closure of ventricular septal defects in childhood - Brown, S.C.; Bruwer, A.D.; Smit, F.E. (SA Heart Journal, 2017)
Ventricular septal defect is the most common congenital cardiac lesion. Surgery was, until recently, the only modality of treatment available. Since the first percutaneous closure was attempted, new devices have been developed and used to close these defects. The procedure is safe and effective if the defects are selected correctly with closure being achieved in more than 90% of patients. Morbidity and mortality are acceptable and comparable to surgery. However, percutaneous ventricular septal defect closure is difficult, technically challenging and should only be attempted in units with adequate experience, equipment and support.